Epidemiological and Lesional Aspects of Traumatic Floating Knees - DOSSOU, FRANCIS MOÏSE DJIDÉNOU; PADONOU, ADEBOLA; AMOSSOU, Labissi François; LAWSON, ERIC; CHIGBLO, SÈGLA PASCAL ERIC; YASSAHOHO, ULRICH (My University, 2017)
The floating knee is a particular lesional entity described for the first time in 1974 by Blake and McBryde and which associates a fracture of the femur with a homolateral fracture of the tibia. This lesion was isolated, among other things, because of its severity. We report in this work the study of a series of 22 cases of floating knee in their epidemiological and lesional aspects. It was a joint retrospective and prospective study covering a period of three and a half years, from 01 January 2013 to 30 June 2016, dealt with at general surgery division of the Department University Hospital of the Ouémé Plateau. The average age in our series was 38.91 years with extremes of 10 and 67 years, the sex ratio was 4.5 in favor of the male sex. All socio-occupational categories were represented with the majority of workers at 31.80%. Highway accidents accounted for 86.40% of the main etiology. Most patients in our series were 68.20% on the left side. The fractures were open in the femur and in the tibia in 22.60% and 72.70%, respectively. We recorded all types of floating knees according to the FRASER classification, with a clear predominance of type I at 81.80%. There has been a steady increase in the recrudescence of floating knees over the years. The floating knee, in our context, is a rare but serious lesion of young adults, favored by the development and the celerity of the means of transport.
Keywords: Floating knee; Ipsilateral fracture